2015
DOI: 10.1177/1350650115594405
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of aluminum matrix functionally graded material: Microstructural and hardness analyses, fretting, fatigue, and mechanical properties

Abstract: This study investigated the mechanical properties of aluminum matrix functionally graded material (FGM) reinforced by integration of aluminum 2014 alloy (AlCu4SiMg) and 15 vol% SiC. The specimens were obtained by centrifugal casting technique, followed by aging treatment. The variations that occurred in microstructure, hardness, Young’s modulus, tensile strength, yield strength, elongation, fatigue, and fretting fatigue behaviors were analyzed. In both cast and aged conditions, it was observed that hardness va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…FGM1's wall thickness was higher than FGM2's. This result is compatible with the previous studies on the subject [74][75][76][77][78][79][80][81][82][83]. Taking into account the wear, fatigue, and fretting behaviors of FGM from previous studies, an aging process was performed (solutionizing at 500 °C, followed by water quenching and reheating for aging at 145 °C for 10 h, followed by water cooling) [75,82,83].…”
Section: Experimental Results and Analysissupporting
confidence: 88%
“…FGM1's wall thickness was higher than FGM2's. This result is compatible with the previous studies on the subject [74][75][76][77][78][79][80][81][82][83]. Taking into account the wear, fatigue, and fretting behaviors of FGM from previous studies, an aging process was performed (solutionizing at 500 °C, followed by water quenching and reheating for aging at 145 °C for 10 h, followed by water cooling) [75,82,83].…”
Section: Experimental Results and Analysissupporting
confidence: 88%
“…However, those functions must reflect the actual distribution of inclusions along the wall thickness, and in many cases simple functions are not able to represent well the measured data. The parametric study was based Latin American Journal of Solids and Structures, 2019, 16(4), e187 11/15 upon the volume fraction profiles obtained from Ulukoy et al (2016) and shown in Figure 5. The material properties are given in Table 1.…”
Section: Parametric Studymentioning
confidence: 99%
“…Therefore, more effective casting methods were used, such as the centrifugal casting of such alloys as AA356, AA413 and AA390 to achieve the effect of grading the content of Si from hypoeutectic to hypereutectic [5]. Moreover, AA2014-SiC centrifugal cast and aged FGMs were obtained that allowed an improvement in their hardness and resistance to fatigue as compared to their standard cast states [6]. The wear resistance and strength characteristics of AA6061 and AA6061/SiC FGMs were also improved by centrifugal casting [7].…”
Section: Introductionmentioning
confidence: 99%